The emerging landscapes to drug delivery systems for the treatment of pancreatic cancer - Magri, Agnes [UNESP]; Baveloni, Franciele Garcia [UNESP]; de Camargo, Bruna Almeida Furquim [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2021)
Pancreatic Ductal Adenocarcinoma (PDA) is a highly metastatic tumor, and the liver is its first target, which restricts the use of medications. PDA is considered one of the most aggressive types of cancer in the world, with an extremely short survival time, depending on the stage of diagnosis. In non-surgical cases, chemotherapy alterna-tives are only effective in 40% to 60% of patients. The low efficiency of treatments oc-curs mainly due to the complex microenvironment in PDA, leading to chemoresistance to treatments and making it difficult to reach the affected tissue. A very important histo-logical characteristic of PDA is the extremely dense stroma, which leads to low vascu-larization of tumor tissue. Consequently, the stroma environment causes less drug accumulation in tumor cells, even of selective and/or targeted drugs. Overcoming the stroma's microenvironment is a major challenge for therapies. Moreover, specific genes lead to di-rect chemoresistance in PDA due to their high progression. In this scenario, nanotechnol-ogy appears as an alternative to overcome these clinical challenges concerning two dist-inct ways: acting on the stroma or/and acting directly on the pancreatic tumor cells. Thus, this review aimed to highlight advances in the application of nanotechnology aiming to open up new landscapes against PDA. There are a huge number of nanoparticles carrying drugs in preclinical and clinical trials for the effective treatment of PDA. These works have been discussed, and based on the current scenario, the future prospects for an efficient treatment of PDA have been proposed.
Keywords: Drug delivery; Nanoparticles; Nanotechnology; Pancreatic ductal adenocarcinoma; Solid tumor; Stroma